Evaluasi Penatausahaan Barang Milik Daerah pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kabupaten Minahasa Tenggara - Koyong, Bella Elisabeth; Afandi, Dhullo; Datu, Christian (Riset Akuntansi dan Portofolio Investasi, 2025)
The administration of regional property is an essential component of regional asset management, ensuring that government-owned assets are utilized efficiently to support public programs and services. Key elements of this administration include bookkeeping, inventory, and reporting, all of which must adhere to applicable laws and regulations. This study aims to evaluate the implementation of regional property administration based on the Regulation of the Minister of Home Affairs No. 47 of 2021 at the Financial Management and Regional Revenue Agency of Southeast Minahasa Regency. Using a qualitative descriptive approach, data were collected through interviews and document analysis. The findings reveal that the agency has generally complied with the regulatory requirements, particularly in the areas of accurate bookkeeping, systematic inventory control, and timely reporting. However, challenges remain in optimizing data input and system infrastructure. This research highlights the need for continuous system improvements and capacity building to enhance the accountability and transparency of regional asset management.